Synergistic Effects of Erzhi Pill Combined With Methotrexate on Osteoblasts Mediated via the Wnt1/LRP5/β-Catenin Signaling Pathway in Collagen-Induced Arthritis Rats - Li, Xiaoya; Lu, Xiangcheng; Fan, Danping; Li, Li; Lu, Cheng; Tan, Yong; Xia, Ya; Zhao, Hongyan; Fan, Miaoxuan; Xiao, Cheng (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease characterized by chronic synovitis, bone erosion and bone loss. Erzhi Pill (EZP), a classic Chinese patent medicine, is often used to treat osteoporosis and shows a capacity for bone metabolism regulation. Methotrexate (MTX), an essential drug for RA treatment, has been reported to inhibit generalized bone loss in RA patients. However, the combined therapeutic effects and mechanism of EZP and MTX in RA have not been fully elucidated. The aim of this study was to investigate the synergistic effect of EZP and MTX on RA and to explore the underlying mechanism through network pharmacological prediction and experimental verification. Chemical compounds of EZP, human target proteins of EZP and MTX, and RA-related human genes were identified in the Encyclopedia of Traditional Chinese Medicine database, PubChem database and NCBI database, respectively. The molecular network of EZP and MTX in RA was generated and analyzed with Ingenuity Pathway Analysis software according to datasets. Then, MTX monotherapy, EZP monotherapy and combined MTX and EZP therapy were administered to collagen-induced arthritis rats, followed by assessment of pathological score, bone damage, bone alkaline phosphatases (BALP) and tartrate resistant acid phosphatase (TRACP), and genes related to the Wnt1/LRP5/β-catenin pathway according to network pharmacological analysis. Finally, serum samples from MTX-, EZP- and MTX+EZP-treated rats were used to treat the rat osteoblast (OB)-like UMR-106 cell line to evaluate genes related to Wnt1/LRP5/β-catenin. Network pharmacological analysis showed that the Wnt/β-catenin signaling pathway was the top shared signaling pathway among MTX, EZP and RA. The results from in vivo experiments indicated that EZP combined with MTX reduced arthritis severity, alleviated ankle bone damage, increased BALP and decreased TRACP serum levels, and regulated the mRNA expression of Wnt1, LRP5, β-catenin, Runx2, BALP and BGP in the ankles. In vitro experiments showed that EZP combined with MTX could also improve gene expression related to the Wnt1/LRP5/β-catenin pathway. This study demonstrated that EZP combined with MTX played a synergistic role in regulating OBs in RA, which was connected with the modulatory effect of EZP and MTX on the Wnt1/LRP5/β-catenin signaling pathway.